Changing differences : women and the shaping of American foreign policy, 1917-1994 - Jeffreys-Jones, Rhodri (Rutgers University Press, 1995)
There are more than fifty women in the United States Congress and nearly one-fourth of foreign service posts are held by women. Nevertheless, the United States has yet to entrust a senior foreign policy job, outside of the United Nations, to a woman. Beneath these statistics lurk central myths that Jeffreys-Jones cogently identifies and describes: the "Iron Lady"--Too masculine; the "lover of peace" - too "pink"; the weak or the promiscuous. These are to name only a few. With an eye to the feminist foreign policy leaders of the future, the author traces the successes and failures of collectivities such as Women Strike for Peace and individuals who were influential in international politics since World War I, including Alice Paul, Jane Addams, Jeannette Rankin, Dorothy Detzer, Eleanor Roosevelt, Margaret Chase Smith, Helen Gahagan Douglas, Bella Abzug, Margaret Thatcher, and many others.